Caracterização do esgoto sanitário e lodo proveniente de reator anaeróbio e de lagoas de estabilização para avaliação da eficiência na remoção de contaminantes - Lopes, Thiara Reis (2015)
The Wastewater Treatment Plants (WWTPs) are used in order to simulate the natural degradation phenomena using controlled conditions to promote sewage treatment, a byproduct called sewage sludge is produced during this process, this is one blend of organic and inorganic material, it was accumulated in the system during the sewage treatment process. The sewage and sludge characteristics are related to human activities, weather conditions. Technological advances can contribute to the insertion of some compounds that are difficult to degrade, rarely treated and removed by conventional methods. This research aims to evaluate the sewage and sludge characteristics, estimating the efficiency of two conventional treatment systems and verify the agricultural potential use of sludge produced. For this, were determined in the influent and effluent of the biological systems of wastewater treatment some physico-chemical parameters (pH, temperature, Dissolved Oxygen (DO), total solids, total fixed solids, total volatile solids, settleable solids, chemistry oxygen demand (COD), ammonia nitrogen). In the sludge were determined physico-chemical parameters (pH, total solids, total fixed solids, total volatile solids, total phosphorus, total K, metals, humidity, organic matter and total organic carbon) and biological (CTT, E. coli, Salmonella sp.). The isolates of E. coli and Salmonella sp. were tested to antimicrobial agents. The results indicated the pH in sewage was near to neutrality and optimum temperatures for bacterial activities. By comparing the treatment systems, the WWTP operated with ponds was more efficient in ammonia nitrogen conversion, removing solids and less efficient in reducing COD. All results were below the limits established by law, except ammonia nitrogen and in some samples the DO and COD. The pH in sludge was slightly acid and near neutrality. The concentration of phosphorus, potassium and organic material in the sludge collected in the system operated with RALF exceeded the system operated with ponds. The concentrations of metal ions in sludge of RALF were higher than those of the sludge drying bed, in ponds the concentrations decreased during the treatment process, to compare the WWTPs, the concentrations of metal ions were higher in RALF sludge, except Mn and Ni, and the Fe concentration was similar. In the sludge of RALF, in the drying bed and ponds were detected Salmonella sp. resistant to amoxicillin (10µg), tetracycline (30µg) and cephalothin (30µg). The E. coli were susceptible only to gentamicin. This study evaluated the efficiency of these conventional systems applied in sewage treatment, the results suggest the need to use appropriate methods of treatment to removal of these antibiotics and inactivation the pathogenic microorganisms, this indicate a potential hazard of these WWTPs in the dispersion of the environment.